Immunologic investigations into transgene directed immune-mediated myositis following delandistrogene moxeparvovec gene therapy - Rachael A. Potter; Ida H. Moeller; Sohrab Khan; Hélène Haegel; Andreas Hollenstein; Guido Steiner; Christoph Wandel; Alexander P. Murphy; Damon R. Asher; Emanuel Palatinsky; Danielle A. Griffin; Stefanie Mason; et al. (Scientific Reports)
Abstract Delandistrogene moxeparvovec is an rAAVrh74 vector-based gene transfer therapy that delivers a transgene encoding delandistrogene moxeparvovec micro-dystrophin, an engineered, functional form of dystrophin shown to stabilize or slow disease progression in DMD. It is approved in the US and in other select countries. Two serious adverse event cases of immune-mediated myositis (IMM) were reported in the phase Ib ENDEAVOR trial (NCT04626674). We hypothesized that immune responses to the micro-dystrophin transgene product may have mediated these IMM events. An interferon-gamma ELISpot assay was used to detect T cell responses to delandistrogene moxeparvovec micro-dystrophin peptide pools. ELISpot analysis suggested that IMM resulted from T cell-mediated responses directed against specific micro-dystrophin peptides corresponding to exons 8 and 9 (Case 1) and exon 8 (Case 2) of the DMD gene. In silico epitope mapping based on the patients’ HLA-I alleles indicated greater probability for peptides derived from exons 8 and/or 9 to bind HLA-I, providing further evidence that peptides derived from corresponding micro-dystrophin regions may have higher immunogenic potential. Collectively, these data suggest that patients with DMD gene deletions involving exons 8 and/or 9 may be at increased risk of IMM following delandistrogene moxeparvovec micro-dystrophin gene therapy infusion.